The Cerebellar Dopaminergic System - Flace, Paolo; Livrea, Paolo; Basile, Gianpaolo Antonio; Galletta, Diana; Bizzoca, Antonella; Gennarini, Gianfranco; Bertino, Salvatore; Branca, Jacopo Junio Valerio; Gulisano, Massimo; Bianconi, Simona; Bramanti, Alessia; Anastasi, Giuseppe (Frontiers in Systems Neuroscience, 2021)
In the central nervous system, dopamine is involved in motor and cognitive functions. Although, the cerebellum is not been considered an elective dopaminergic region, studies attributed to it a critical role in dopamine deficit related neurological and psychiatric disorders (e.g. Parkinson’s disease, schizophrenia). Data on the cerebellar dopaminergic neuronal system are still lacking. Nevertheless, in studies midbrain cerebellar dopaminergic afferents as well as the dopaminergic receptor subtypes (DRD1-DRD5) has been demonstrated. Moreover, biochemical studies detected in the mammalians cerebellum high dopamine levels, while chemical neuroanatomy studies revealed in the deep cerebellar nuclei and in several lobules of the cerebellar cortex a relatively low number of dopaminergic neuronal cell bodies and processes. The present review summarizes the data on the cerebellar dopaminergic system including its involvement in associative and projective cerebellar circuits. Furthermore, this study also briefly, discuss the role of the cerebellar dopaminergic system in some neurologic and psychiatric disorders, and suggest its potential involvement as target in pharmacologic and non-pharmacologic treatments.